Spatial and temporal patterns in the coral assemblage at Clipperton Atoll: a sentinel reef in the Eastern Tropical Pacific - J. J. Adolfo Tortolero-Langarica; Eric Clua; Fabián A. Rodríguez-Zaragoza; Jennifer E. Caselle; Alma P. Rodríguez-Troncoso; Mehdi Adjeroud; Alan M. Friedlander; Amílcar L. Cupul-Magaña; Enric Ballesteros; Juan P. Carricart-Ganivet; Eric K. Brown (Coral Reefs, 2022)

Juvenile corals underpin coral reef carbonate production after disturbance - Jérémy Carlot; Mohsen Kayal; Hunter S. Lenihan; Simon J. Brandl; Jordan M. Casey; Mehdi Adjeroud; Ulisse Cardini; Alexandre Merciere; Benoit Espiau; Diego R. Barneche; Alessio Rovere; Laetitia Hédouin; et al. (Global Change Biology, 2021)
Sea‐level rise is predicted to cause major damage to tropical coastlines. While coral reefs can act as natural barriers for ocean waves, their protection hinges on the ability of scleractinian corals to produce enough calcium carbonate (CaCO 3 ) to keep up with rising sea levels. As a consequence of intensifying disturbances, coral communities are changing rapidly, potentially reducing community‐level CaCO 3 production. By combining colony‐level physiology and long‐term monitoring data, we show that reefs recovering from major disturbances can produce 40% more CaCO 3 than currently estimated due to the disproportionate contribution of juvenile corals. However, the buffering effect of highly productive juvenile corals is compromised by recruitment failures, which have been more frequently observed after large‐scale, repeated bleaching events. While the size structure of corals can bolster a critical ecological function on reefs, climate change impacts on recruitment may undermine this buffering effect, thus further compromising the persistence of reefs and their provision of important ecosystem services.

Recurrent disturbances, recovery trajectories, and resilience of coral assemblages on a South Central Pacific reef - M. Adjeroud; F. Michonneau; P. J. Edmunds; Y. Chancerelle; T. Lison de Loma; L. Penin; L. Thibaut; J. Vidal-Dupiol; B. Salvat; R. Galzin (Coral Reefs, 2009)

High latitude, high coral diversity at Rapa, in southernmost French Polynesia - M. Adjeroud; M. Pichon; C. C. Wallace (Coral Reefs, 2009)

High genetic diversity of the symbiotic dinoflagellates in the coral Pocillopora meandrina from the South Pacific - H. Magalon; E. Baudry; A. Husté; M. Adjeroud; M. Veuille (Marine Biology, 2006)

Sexual reproduction of Acropora reef corals at Moorea, French Polynesia - A. Carroll; P. Harrison; M. Adjeroud (Coral Reefs, 2006)

Patterns of genetic variation do not correlate with geographical distance in the reef‐building coral Pocillopora meandrina in the South Pacific - H. MAGALON; M. ADJEROUD; M. VEUILLE (Molecular Ecology, 2005)
Dispersal may be a critical factor in the ability of reef‐building corals to recover after major disturbances. We studied patterns of geographical structure using four microsatellite markers in seven South Pacific populations of Pocillopora meandrina, a major coral species from Polynesia. Variation within populations showed evidence of heterozygote deficiency. Genetic differentiation between populations was detected at a large scale (2000 km) between the Tonga and the Society Islands. Within the Society Islands, four of the five studied populations from Bora Bora, Moorea and Tahiti were not significantly different from each other. Unexpectedly, one of the three populations surveyed in Moorea was genetically different from the other two populations of this island (that were 5 and 10 km apart), and from the populations of the other two surveyed islands in this archipelago. We cannot rule out the possibility that this pattern is an equilibrium state, whereby short‐range dispersal is locally more differentiating than long‐range dispersal, as has been suggested by similar patterns reported in other studies. An alternative explanation that is globally consistent with all observations is that this is the signature of a large‐scale destruction event, as for instance a bleaching event, followed by the recent restoration of populations by new colonists.

Genetic variation and clonal structure in the scleractinian coral Pocillopora damicornis in the Ryukyu Archipelago, southern Japan - M. Adjeroud; M. Tsuchiya (Marine Biology, 1999)

Objectives and background to the 1994 Franco-Australian expedition to Taiaro Atoll (Tuamotu Archipelago, French Polynesia) - R. Galzin; S. Planes; M. Adjeroud; C. Chauvet; P. J. Doherty; J. Poupin (Coral Reefs, 1998)